Awareness of Oral Health Changes during Menstruation: A Questionnaire-Based Survey among Adolescent Girls - Sheiba R Gomes; Sandhya Tamgadge; Siddharth S Acharya; Prem R Thapar; Rutika R Patil; Sneha C Khanapure (Wolters Kluwer Medknow Publications, 2019)
Background: Periodontal health in women is affected by sex hormones. Puberty, menstruation, use of oral contraceptives, pregnancy, and menopause influence the periodontal health in women. Aim: This study was conducted to assess the awareness of oral health changes during menstruation in adolescent girls. Materials and Methods: A self-administered cross-sectional survey was conducted at a node in Navi Mumbai to assess the awareness of adolescent school-going girls on the subject of menstruation and the oral changes associated with the same. Results: Majority of the participants were aware of menstruation and associated problems, but only 4% of participants were aware that oral health changes can occur during menstruation. Conclusion: There is a definite lacuna in the awareness of adolescents about menstruation and the oral health changes associated with the same, and creating awareness on this association is necessary to prevent periodontal disease in adulthood.